A educação do campo e a realidade do município de Vitória da Conquista (BA) - Ramal, Camila Timpani (Universidade Federal de São Carlos, 2010)
This paper studies the historical background of countrified education in Brazil, recovering in national history a context of great debate about the ideal conditions for man setting the field, stated by the ruralists educational thinkers in the early Republican period in Brazil and how this thinking is still present in countrified education in the town of Vitoria da Conquista, BA. The final considerations of this research pointed out that nowadays it is still possible to verify in the educational reality of the aforementioned city remains of the educational ideas advocated by countrified educators of the early twentieth century.
Keywords: Educação rural; Ruralismo pedagógico; CIENCIAS HUMANAS::EDUCACAO